1974
DOI: 10.2134/agronj1974.00021962006600040016x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Altitude on Seed Yield and Other Characters of Soybeans Differing in Maturity in Sikkim (Himalayan Kingdom)1

Abstract: A need exists for information on effects of altitude on yield and other characteristics of soybeans (Glycine max (L.) Merr.). Accordingly we evaluated the response of several imported varieties and a local variety for 2 years at altitudes of 1,394 and 1,636 m. Soybean growth and development was retarded at the higher altitude, and plants were shorter, lodged less, and had fewer nodes. Seeds with better quality were produced at the higher altitude. Seed weight varied with years at the two altitudes. Yield of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
2

Year Published

1978
1978
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
2
4
0
2
Order By: Relevance
“…Altitude, daylength, maximum temperature, and minimum temperature were significantly correlated with number of days to flcwer. Increased altitude resulted in a greater number of days to flower, which agrees with the results of B::.snet et al (2). Increased daylength at the time of flc•wering was also associated with a greater number of days to flower, a result which agrees with numerous re:)orts (1, 3,6,10,11,12).…”
Section: Resultssupporting
confidence: 89%
“…Altitude, daylength, maximum temperature, and minimum temperature were significantly correlated with number of days to flcwer. Increased altitude resulted in a greater number of days to flower, which agrees with the results of B::.snet et al (2). Increased daylength at the time of flc•wering was also associated with a greater number of days to flower, a result which agrees with numerous re:)orts (1, 3,6,10,11,12).…”
Section: Resultssupporting
confidence: 89%
“…The writer related the disease situation to storage life of the soybean under tropical conditions in Puerto Rico and concluded that soybean fields used for producing seeds should be located in areas where dry conditions prevail during maturation of the seeds. Basnet et al (1974) reached the same conclusion from a two-year study in Sikkim (Hilalayan Kingdom) . The later maturing cultivar which matured during favorable harvest weather produced good seed quality.…”
supporting
confidence: 64%
“…1 The poor performance of these maturity group V through VII cultivars at 14°and 22°was associated with their early flowering. Other studies demonstrating that early-maturing cultivars are poorly adapted to low latitude environments include Barrios (1961) Barrios and Ortega (1968); Camacho et al (1974); Basnet et al (1974) ; and Beard et al (1980) In 1973 and 1974, the material provided by INTSOY was studied at Tampico,Tamaulipas, and the Jupiter cultivar (included in the INTSOY trails) was more promising than Tropicana, the cultivar being grown by farmers in the Tampico area.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In any given condition, the modification of the relative lengths of vegetative and reproductive periods may enable the reproductive period to be under favourable photoperiod and result in improvement of yield components (Schweitzer and Harper 1985), chemical compositions (Han et al. 1997), and resistances to environmental stresses (Basnet et al. 1974; Mayers et al.…”
Section: Discussionmentioning
confidence: 99%
“…In soya bean, post-flowering SD can increase 100-seed weight (Han et al 1996), and change protein content (higher under SD than under LD), oil content (lower under SD than under LD) and fatty acid profile (Han et al 1997). In any given condition, the modification of the relative lengths of vegetative and reproductive periods may enable the reproductive period to be under favourable photoperiod and result in improvement of yield components (Schweitzer and Harper 1985), chemical compositions (Han et al 1997), and resistances to environmental stresses (Basnet et al 1974;Mayers et al 1991;Mac¸a˜s et al 1996) of crops. As the differences in the duration of pre-or post-flowering developmental phases among soya bean varieties depended on photoperiod sensitivity at the corresponding phases (Han et al 1998), the genetic improvement of the ratio of vegetative to reproductive phase should result from the modification of photoperiod sensitivity at vegetative as well as the reproductive phase.…”
Section: Discussionmentioning
confidence: 99%